2019
DOI: 10.1111/anae.14584
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for compromised data integrity in studies of liberal peri‐operative inspired oxygen

Abstract: SummaryIn 2016 the World Health Organization recommended intra‐operative ventilation with 80% inspired oxygen to reduce surgical site infection rates, based upon a meta‐analysis of 15 randomised controlled trials, of which two were by Mario Schietroma's research group. Five trials by this group have been retracted for duplication, plagiarism, statistical error and lack of ethical approval. We analysed 40 papers by this group: 24 randomised controlled trials (5064 participants) and 16 observational studies (184… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…Among the coauthors of the review published in Anaesthesia 2 is John Carlisle, a consultant anaesthetist at Torbay Hospital in Devon, UK, who has pioneered statistical studies of the baseline data of participants in trials that can show whether they are inconsistent with participants chosen randomly, as they should be. The team also checked the calculations of P values and found that a high proportion had been miscalculated—324 of 825.…”
Section: Retracted Papermentioning
confidence: 99%
“…Among the coauthors of the review published in Anaesthesia 2 is John Carlisle, a consultant anaesthetist at Torbay Hospital in Devon, UK, who has pioneered statistical studies of the baseline data of participants in trials that can show whether they are inconsistent with participants chosen randomly, as they should be. The team also checked the calculations of P values and found that a high proportion had been miscalculated—324 of 825.…”
Section: Retracted Papermentioning
confidence: 99%
“…Anaesthesia has an active social media presence, with initiatives including a regular ‘TweetChat’, where interested parties, including authors, are brought together on one platform to discuss a newly published paper . The recent #Hyperoxia TweetChat, on a paper about evidence for compromised data integrity in studies of liberal peri‐operative inspired oxygen , generated ~60,000 impressions (the number of times Tweets from @Anaes_Journal were seen) on the day of publication. Such initiatives must surely increase attention, citations and the speed with which the benefits from scientific research yield improvements in clinical care, but social media analytics is a new science and it is not yet clear how these metrics should be interpreted.…”
mentioning
confidence: 99%
“…In February 2019, data integrity from 38 published randomised controlled trials in surgical patients conducted by an Italian surgical research group was called into question (Buranyi and Devlin 2019). Using the Carlisle method, Myles, Carlisle and Scarr identified evidence of compromised data in 38 out of 40 published articles from Mario Schietroma’s research group spanning from years 1993 to 2016 (Myles et al 2019). In their analysis, they meta-analysed all published patient characteristic data, identifying poorly distributed participant characteristics, incorrect ‘ p ’ values and overly consistent results.…”
mentioning
confidence: 99%
“…In their analysis, they meta-analysed all published patient characteristic data, identifying poorly distributed participant characteristics, incorrect ‘ p ’ values and overly consistent results. There was enough evidence from this analysis to recommend an inquiry into the group’s work, and their published outputs are likely to have been misleading researchers within the field of perioperative medicine for some years (Myles et al 2019). Such alleged misconduct is not only damaging to the scientific community and to perioperative research, but may also have substantial global consequences for patient safety through the impact of flawed research on doctors’ prescribing habits.…”
mentioning
confidence: 99%